Relationship between subjective masticatory performance assessed by food acceptance questionnaire and comprehensively assessed oral function in older outpatients at a dental hospital in Japan: a cross-sectional study - Ryota Futatsuya; Yohei Hama; Mitsuzumi Okada; Mayuko Matsuzaki; Linjing Xiong; Kohei Yamaguchi; Kanako Noritake; Yoshiyuki Sasaki; Manabu Kanazawa (BMC Oral Health)
Abstract Background With the global rise in the aging population, the relationship between oral function and risk of long-term care is attracting attention. One method for subjective assessment of masticatory function is the use of a food acceptance questionnaire. Although it is hypothesized that objective oral functions such as tongue pressure and swallowing function are associated with subjective masticatory performance, this relationship has yet to be investigated. The aim of this study is to elucidate the association between overall oral function and subjective masticatory performance using a food questionnaire. Methods Patients aged ≥ 65 years were recruited from an outpatient dental clinic at Tokyo Medical and Dental University. Subjective masticatory performance was assessed using the food acceptance score as described in a previous study. Seven oral function parameters defined by the Japanese Society of Gerodontology, were measured. Age, sex, number of functional teeth, geriatric depression, cognitive function, and oral health-related quality of life were assessed. Variables for which normality was rejected were transformed into tertile values. Multiple regression analysis was conducted with the food acceptance score as the objective variable, and each oral function parameter and other items as explanatory variables. Results This study included 201 participants (87 males and 114 females). Multiple regression analysis revealed that the number of functional teeth, geriatric depression, oral health-related quality of life, objective masticatory performance, tongue pressure, and swallowing function were substantially associated with the food acceptance scores. Conclusions This study demonstrated that subjective masticatory performance was independently associated with tongue pressure, objective masticatory performance, swallowing function, number of functional teeth, geriatric depression, and oral health-related quality of life.